Dampak Kualitas Produk Terhadap Loyalitas Melalui Kepuasan Pelanggan Hp Iphone Pada Mahasiswa FEB Unisma Malang - Evi Rahayu; Nur Hidayati; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of product quality on loyalty through customer satisfaction hp iphone. This research is an explanatory research type, with a quantitative approach. The research method used is path analysis. The sampling technique used purposive sampling, the sample determined to be sampled obtained by 48 respondents as a sample. The results of this study show that partially all variables have significant and positive influences. While the results of intervening tests showed that customer satisfaction is able to mediate the relationship between product quality to customer loyalty hp iphone. Keywords: product quality, customer loyalty and customer satisfaction